Association of serial serum major histocompatibility complex class I chain‐related A measurements with hepatocellular carcinoma in chronic hepatitis C patients after viral eradication. Issue 1 (10th July 2018) - Huang, Chung‐Feng; Wang, Shu‐Chi; Yeh, Ming‐Lun; Huang, Ching‐I; Tsai, Pei‐Chien; Lin, Zu‐Yau; Chen, Shinn‐Cherng; Dai, Chia‐Yen; Huang, Jee‐Fu; Chuang, Wan‐Long; Chen, Angela; Yu, Ming‐Lung
Abstract: Background and Aim: Major histocompatibility complex class I chain‐related A (MICA) genetic variants and their serum levels (sMICA) were associated with the development of hepatitis C virus‐related hepatocellular carcinoma (HCC) in untreated cohorts. The dynamic changes in serial sMICA levels and their association with HCC in the post‐curative status are elusive. Methods: Single nucleotide polymorphism rs2596542 of MICA and serial sMICA levels were analyzed in chronic hepatitis C patients with a sustained virologic response after antivirals. Forty‐two patients who developed HCC and 84 age‐matched, gender‐matched, and cirrhosis propensity score‐matched non‐HCC controls were compared. Serial sMICA levels were measured within 6 months before treatment initiation (pre‐sMICA), 6 months after the end of treatment (post‐sMICA), and on the last visit before the development (or not) of HCC (last‐sMICA). Results: Cox regression analysis revealed that last‐sMICA was the only predictive factor of HCC development (hazard ratio/95% confidence interval: 2.27 (per 1 log pg/mL increase)/1.672–3.082, P < 0.001). Patients without HCC development showed a significantly reduced trend of sMICA levels during follow‐up (trend P = 0.001), which was observed only in GG genotype (trend P < 0.001) but not A allele carriers ( P = 0.88). In contrast, patients with HCC showed an increased trend of sMICA levels (trend P = 0.024). However, only the GG genotype "high expressors" (trend P = 0.06) but not A allele carriers ( P = 0.18) showed a correlation of substantially increased trend of sMICA levels and HCC development. Conclusions: Serial sMICA levels were associated with HCC development in SVR patients. The clinical utility of this finding is restricted to MICA rs2596542 GG genotype carriers.